2011
DOI: 10.1159/000328647
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Functional Outcomes of 5-Year Subarachnoid Haemorrhage Survivors: Comparison to Matched Healthy Controls

Abstract: Background and Purpose: While neuropsychological deficits have been the focus of research post-subarachnoid haemorrhage (SAH), population-based information on long-term neuropsychological impairment post-SAH are lacking. Neither the profile of long-term neuropsychological deficits nor its relationship to long-term functional outcomes has been established. Methods: This was a cross-sectional population-based study of long-term (5 years) neuropsychological and functional outcomes post-SAH. Participants were 27 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 55 publications
2
25
0
2
Order By: Relevance
“…Neuropsychological studies of patients with frontal lesions have reported that impaired executive functions due to frontal-lobe damage are associated with decreasing mental HQOL scores (Chahal, Barker-Collo, & Feigin, 2011;Laffond et al, 2012). In previous psychological studies, executive functions showed a positive correlation with psychological attitudes, including satisfaction with life, gratitude, and forgiveness (Kruger, 2011;Miley & Spinella, 2006), where satisfaction with life is regarded as one component of QOL and as one of the most important components affecting HQOL (McAuley et al, 2008;Pavot & Diener, 1993;Rejeski & Mihalko, 2001;Wrosch & Scheier, 2003).…”
Section: Health-related Qol and Cognitive Functionsmentioning
confidence: 98%
“…Neuropsychological studies of patients with frontal lesions have reported that impaired executive functions due to frontal-lobe damage are associated with decreasing mental HQOL scores (Chahal, Barker-Collo, & Feigin, 2011;Laffond et al, 2012). In previous psychological studies, executive functions showed a positive correlation with psychological attitudes, including satisfaction with life, gratitude, and forgiveness (Kruger, 2011;Miley & Spinella, 2006), where satisfaction with life is regarded as one component of QOL and as one of the most important components affecting HQOL (McAuley et al, 2008;Pavot & Diener, 1993;Rejeski & Mihalko, 2001;Wrosch & Scheier, 2003).…”
Section: Health-related Qol and Cognitive Functionsmentioning
confidence: 98%
“…For many patients and their families, the quality of life is as important as prolongation of life. Consequently, maintenance and recovery of damaged neuronal circuits important for everyday life activities such as cognitive and motor functions, speech and memory could be a better measure of a drug efficacy (Chahal et al , 2011; Hutter et al , 1995; Vieira et al , 2011). Thus, for experimental compounds to become a successful therapy in humans, a therapy that goes beyond prevention of cell death and addresses the acute and delayed deficits that affect quality of life of aSAH victims is required.…”
Section: Failure To Translate Successful Animal Therapies To Clinimentioning
confidence: 99%
“…Furthermore, mental slowness and attention deficits are known long-term consequences of A-SAH. 3 Patients who do regain independence for activities of daily life may not be able to resume work, experience difficulties in maintaining and establishing relationships, and report mood disturbances and impaired quality of life 4,5 with long-term anxiety complaints, symptoms of depression, and fatigue. 6,7 However, studies that evaluate the outcomes of SAH survivors beyond the horizon of 1 yr after onset are scarce.…”
mentioning
confidence: 99%